Advanced drug delivery systems for oral squamous cell carcinoma: a comprehensive review of nanotechnology-based and other innovative approaches - Herrada Céspedes, Alain; Reyes, Montserrat; Morales, Javier O. (Frontiers in Drug Delivery, 2025)
Oral cancer, particularly oral squamous cell carcinoma (OSCC), poses significant challenges due to its aggressiveness, high metastatic potential, and resistance to conventional therapies. Recent advancements in drug delivery systems (DDS), including nanotechnology, intelligent hydrogels, lipid nanoparticles, and photodynamic therapy (PDT), offer innovative solutions for targeted treatment. These DDS utilize tumor-specific stimuli, such as pH variations, reactive oxygen species (ROS), and enzymatic activity, to achieve precise drug release while minimizing systemic toxicity. Cutting-edge technologies, such as microelectromechanical systems (MEMS) and artificial intelligence (AI), are enhancing the precision and personalization of DDS. Combination therapies integrating chemotherapy, PDT, and immunotherapy show promise in overcoming current limitations. Despite significant progress, challenges remain in scalability, patient-specific customization, and safety assessments. This review synthesizes the state-of-the-art in DDS for OSCC, highlighting future directions and the need for interdisciplinary collaboration to improve therapeutic outcomes and patient quality of life.